Literasi Digital dan Keuangan Pelaku UMKM Perempuan untuk Keberlanjutan Usaha - Pranitasari, Diah; Suriawinata, Iman Sofian; Adyarini, Kus Tri (LPMP Imperium, 2025)
The digital and financial literacy program for women-owned MSMEs aimed to enhance their ability to leverage digital technology and manage business finances effectively and sustainably. The program was implemented for MSME participants from the School Committee Communication Forum (FKKS) in Ciracas District, held from July 28 to 30, 2025. The method employed was interactive training, combining lectures, discussions, case studies, and hands-on practice using digital tools. Participants also received guidance in preparing financial plans and digital marketing strategies. The success indicators of this program included improved product innovation, the adoption of digital financial applications, and the use of digital marketing. The results showed a significant increase in participants’ understanding of digital media for promotion, application-based financial recording, pricing strategies, and capital management.